Ethnomedicinal insights from the Himalayas: Plants used for gastrointestinal disorders in Sarkaghat tehsil of district Mandi, Himachal Pradesh - Suresh Kumar; Arti Devi (Asian Journal of Pharmaceutical Research and Development, 2026)
The objective of the present study was to document and systematically inventory ethnomedicinal plants traditionally used for the treatment of gastrointestinal disorders in Sarkaghat tehsil of district Mandi, Himachal Pradesh, with the aim of preserving rapidly declining traditional knowledge among local healers. The study was designed as a field-based ethnobotanical investigation using both qualitative and quantitative approaches. Ethnomedicinal information was collected from 100 informants aged 35–70 years through structured questionnaires, personal interviews and participatory observations involving traditional healers and knowledgeable elders. Data on vernacular names, plant parts used, modes of preparation and dosage formulations were documented, and quantitative ethnobotanical indices such as Use Value (UV), Relative Frequency of Citation (RFC) and Fidelity Level (FL) were employed to assess the cultural significance and prominence of recorded plant species. The main outcomes measured included diversity of medicinal plants, patterns of use, preparation methods and quantitative indices reflecting species importance. A total of 27 plant species belonging to 21 families were documented for the treatment of gastrointestinal disorders such as diarrhoea, dysentery, constipation, bloating, gas and abdominal pain. Leaves were the most frequently utilized plant part, followed by fruits, seeds, roots and bark. Decoction was the dominant mode of preparation (33.3%), followed by juice (22.2%), powder (14.8%), raw consumption (11.1%), infusion (3.7%) and food-based preparations (7.4%). The UV ranged from 1.0 to 3.0, with Aloe vera exhibiting the highest value, while RFC values ranged from 0.38 to 0.90. FL values varied from 68.4% to 97.7%, with the highest values recorded for Curcuma longa, Ocimum tenuiflorum, Terminalia chebula and Emblica officinalis. In conclusion, the study highlights the rich ethnomedicinal heritage of Sarkaghat tehsil and underscores the urgent need for phytochemical and pharmacological validation of culturally significant plant species to facilitate their integration into evidence-based healthcare systems.